2014
DOI: 10.1155/2014/456848
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Functionally Graded Coatings in Contact with Cylindrical Rollers

Abstract: This work presents finite element analysis (FEA) and results for rolling contact of a cylindrical roller on an elastic substrate coated by functionally graded material (FGM). The rolling process and the graded coating material property and layers arrangement are modeled using finite element codes which lead to a new methodology. This novel methodology provides a trend in determining surface contact stresses, deformations, contact zones, and energy dissipation through the contact area. Effects of stiffness rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Rather often, the initiation of the gradient coating destruction is caused by contact or localized loads. Therefore, in the last decade, the analysis of mechanical stresses in protective coatings caused by contact pressure has been the subject of research by many scientists [44][45][46][47][48]. These papers demonstrate the effects of factors such as coating stiffness, friction coefficient and contact geometry on the stress state of coatings and substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Rather often, the initiation of the gradient coating destruction is caused by contact or localized loads. Therefore, in the last decade, the analysis of mechanical stresses in protective coatings caused by contact pressure has been the subject of research by many scientists [44][45][46][47][48]. These papers demonstrate the effects of factors such as coating stiffness, friction coefficient and contact geometry on the stress state of coatings and substrates.…”
Section: Introductionmentioning
confidence: 99%
“…The hierarchical structure from SS316L to Inconel 718 to copper based on SS304L substrate was achieved by a DED system 18 . Stress distribution predicted by Finite Element Method (FEM) will be instructive when making material selection and design 19 . DED can also be used for surface coating, part maintenance, and the repair of defects such as cavities, cracks, and delamination 20 22 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study revealed that a coating film can improve elastic modulus of BCC lattice structure up to 68 percent [14]. The general stress analysis of coated lattice structures was already studied through analytical [15], numerical [16], [17], or experimental [18] approach. In analytical and numerical methods, lattice is treated as a special type of composites, whose equivalent properties are common to be mapped from local to global level.…”
Section: Introductionmentioning
confidence: 99%